The High Cost of Free Tuberculosis Services: Patient and Household Costs Associated with Tuberculosis Care in Ebonyi State, Nigeria - Ukwaja, Kingsley N. (Public Library of Science, 2013)
OBJECTIVE: Poverty is both a cause and consequence of tuberculosis. The objective of this study is to quantify patient/household costs for an episode of tuberculosis (TB), its relationships with household impoverishment, and the strategies used to cope with the costs by TB patients in a resource-limited high TB/HIV setting. METHODS: A cross-sectional study was conducted in three rural hospitals in southeast Nigeria. Consecutive adults with newly diagnosed pulmonary TB were interviewed to determine the costs each incurred in their care-seeking pathway using a standardised questionnaire. We defined direct costs as out-of-pocket payments, and indirect costs as lost income. RESULTS: Of 452 patients enrolled, majority were male 55% (249), and rural residents 79% (356), with a mean age of 34 (±11.6) years. Median direct pre-diagnosis/diagnosis cost was $49 per patient. Median direct treatment cost was $36 per patient. Indirect pre-diagnostic and treatment costs were $416, or 79% of total patient costs, $528. The median total cost of TB care per household was $592; corresponding to 37% of median annual household income pre-TB. Most patients reported having to borrow money 212(47%), sell assets 42(9%), or both 144(32%) to cope with the cost of care. Following an episode of TB, household income reduced increasing the proportion of households classified as poor from 54% to 79%. Before TB illness, independent predictors of household poverty were; rural residence (adjusted odds ratio [aOR] 2.8), HIV-positive status (aOR 4.8), and care-seeking at a private facility (aOR 5.1). After TB care, independent determinants of household poverty were; younger age (≤35 years; aOR 2.4), male gender (aOR 2.1), and HIV-positive status (aOR 2.5). CONCLUSION: Patient and household costs for TB care are potentially catastrophic even where services are provided free-of-charge. There is an urgent need to implement strategies for TB care that are affordable for the poor.